Estudio de prefactibilidad para la instalación de una planta de fabricación de prendas médicas desechables - Cabrera Guerrero, Cinthia Veronica (2018)
The present work aims to evaluate the feasibility of setting up a factory to produce disposable uniforms for the health sector. At present, there is a great amount of procedures and services of the health sector that require the use of protective clothing against the biological risk, for patients and people of attention. Faced with this need, a better option of clothing was analyzed in addition to those already existing in the health sector. This led to the initiative to evaluate the feasibility of implementing a factory to produce disposable uniforms, which represent an innovative idea to offer a product with differentiated characteristics.